The oxygen-conserving potential of the diving response: A kinetic-based analysis. Issue 7 (3rd April 2017) - Costalat, Guillaume; Coquart, Jeremy; Castres, Ingrid; Joulia, Fabrice; Sirost, Olivier; Clua, Eric; Lemaître, Frédéric
ABSTRACT: We investigated the oxygen-conserving potential of the human diving response by comparing trained breath-hold divers (BHDs) to non-divers (NDs) during simulated dynamic breath-holding (BH). Changes in haemodynamics [heart rate (HR), stroke volume (SV), cardiac output (CO)] and peripheral muscle oxygenation [oxyhaemoglobin ([HbO2 ]), deoxyhaemoglobin ([HHb]), total haemoglobin ([tHb]), tissue saturation index (TSI)] and peripheral oxygen saturation (SpO2 ) were continuously recorded during simulated dynamic BH. BHDs showed a breaking point in HR kinetics at mid-BH immediately preceding a more pronounced drop in HR (−0.86 bpm.% −1 ) while HR kinetics in NDs steadily decreased throughout BH (−0.47 bpm.% −1 ). By contrast, SV remained unchanged during BH in both groups (all P  > 0.05). Near-infrared spectroscopy (NIRS) results (mean ± SD) expressed as percentage changes from the initial values showed a lower [HHb] increase for BHDs than for NDs at the cessation of BH (+24.0 ± 10.1 vs. +39.2 ± 9.6%, respectively; P  < 0.05). As a result, BHDs showed a [tHb] drop that NDs did not at the end of BH (−7.3 ± 3.2 vs. −3.0 ± 4.7%, respectively; P  < 0.05). The most striking finding of the present study was that BHDs presented an increase in oxygen-conserving efficiency due to substantial shifts in both cardiac and peripheral haemodynamics during simulated BH. In addition, the kinetic-based approach we used provides further credence to the concept of an "oxygen-conserving breaking point" in the human diving response.